Burn injury in senior citizens over 75 years of age - Klosová, Hana; Tymonová, Jarmila; Adámková, Monika (Acta chirurgiae plasticae (English ed.), 2005)
This is a retrospective analysis of a group of 67 senior citizens over 75 years of age who had been hospitalized at the Burn Center of the FNsP Hospital in Ostrava – Poruba in the years 1999 – 2003.We have studied a group of males and females, noting their average age, most common causes of burn injuries, mechanisms of burn injuries, average extent of burn injuries, and most commonly burned body parts.We have also reviewed the seriousness of burn injury in senior citizens, factors that complicated the course of treatment as well as its impact on the final therapeutic effect. The importance of specific approach and individual therapeutic strategy is emphasized. We would also like to emphasize the need for complex therapy approach due to secondary diseases that are very common in this age group. The treatment of burn patients in this age group is very challenging from a personal and economic point of view. The goals of therapy are a full recovery and the return of the patient to normal life. However, goals and therapeutic results are determined and limited by the above-mentioned factors. Nevertheless, every therapeutic success, although partial, should be perceived as positive. For the patient, every success from the point of view of the ability to take care of himself or herself and the overall quality of life is fundamental.
Keywords: Humans; lidé; senioři; péče o pacienty v kritickém stavu; popálení; Aged; Burns; Critical Care